Lymphocyte trajectories are associated with prognosis in critically ill patients: A convenient way to monitor immune status - Pei, Fei; Song, Wenliang; Wang, Luhao; Liang, Liqun; Gu, Bin; Chen, Minying; Nie, Yao; Liu, Yishan; Zhou, Yu; Guan, Xiangdong; Wu, Jianfeng (Frontiers in Medicine, 2022)
Background:Immunosuppression is a risk factor for poor prognosis of critically ill patients, but current monitoring of the immune status in clinical practice is still inadequate. Absolute lymphocyte count (ALC) is not only a convenient biomarker for immune status monitoring but is also suitable for clinical application. In this study, we aimed to explore different trajectories of ALC, and evaluate their relationship with prognosis in critically ill patients. Methods:We retrospectively enrolled 10,619 critically ill patients admitted to a general intensive care unit (ICU) with 56 beds from February 2016 to May 2020. Early dynamic ALC was defined as continuous ALC from before ICU admission to 5 days after ICU admission. Initial ALC was defined as the minimum ALC within 48 hours after ICU admission, and ALC slope was defined as the slope from the initial to that 5 days after ICU admission. Group-based trajectory modeling (GBTM) was used to group critically ill patients according to early dynamic ALC. A combined outcome included persistent inflammation, immunosuppression, catabolism syndrome (PICS), hospital mortality and 28-day mortality. Results:A total of 2022 critically ill patients were unsupervisedly divided into four endotypes based on early ALC, including persistent lymphopenia endotype (n=1211; 58.5%), slowly rising endotype (n=443; 22.6%), rapidly decreasing endotype (n=281; 14.5%) and normal fluctuation endotype (n=87; 4.4%). Among the four trajectory endotypes, the persistent lymphopenia endotype had the highest incidence of PICS (24.9%), hospital mortality (14.5%) and 28-day mortality (10.8%). In a multiple logistic regression, early persistent lymphopenia was associated with poor combined outcome (odd ratio [OR]: 1.54; 95% confidence interval [CI]: 1.13–2.13) in critically ill patients, while initial severe lymphopenia (OR: 0.90; 95% CI: 0.66–1.23) and descending ALC slope (OR: 0.92; 95% CI: 0.70–1.21) were not. Sensitivity analysis further confirmed that the ALC trajectory model of non-infected patients and non-elderly patients can accurately distinguished 91% and 90% of critically ill patients into the same endotypes as the original model, respectively. Conclusions:The ALC trajectory model is helpful for grouping critically ill patients, and early persistent lymphopenia is associated with poor prognosis. Notably, early persistent lymphopenia may be a robust signal of immunosuppression in critically ill patients.